Manganese Peroxidase-Dependent Oxidation of Glyoxylic and Oxalic Acids Synthesized by Ceriporiopsis subvermispora Produces Extracellular Hydrogen Peroxide - Urzúa, Ulises (American Society for Microbiology, 1998)
The ligninolytic system of the basidiomycete Ceriporiopsis subvermispora is composed of manganese peroxidase (MnP) and laccase. In this work, the source of extracellular hydrogen peroxide required for MnP activity was investigated. Our attention was focused on the possibility that hydrogen peroxide might be generated by MnP itself through the oxidation of organic acids secreted by the fungus. Both oxalate and glyoxylate were found in the extracellular fluid of C. subvermispora cultures grown in chemically defined media, where MnP is also secreted. The in vivo oxidation of oxalate was measured; (14)CO(2) evolution was monitored after addition of exogenous [(14)C]oxalate to cultures at constant specific activity. In standard cultures, evolution of CO(2) from oxalate was maximal at day 6, although the MnP titers were highest at day 12, the oxalate concentration was maximal (2.5 mM) at day 10, and the glyoxylate concentration was maximal (0.24 mM) at day 5. However, in cultures containing low nitrogen levels, in which the pH is more stable, a better correlation between MnP titers and mineralization of oxalate was observed. Both MnP activity and oxidation of [(14)C]oxalate were negligible in cultures lacking Mn(II). In vitro assays confirmed that Mn(II)-dependent oxidation of [(14)C]oxalate by MnP occurs and that this reaction is stimulated by glyoxylate at the concentrations found in cultures. In addition, both organic acids supported phenol red oxidation by MnP without added hydrogen peroxide, and glyoxylate was more reactive than oxalate in this reaction. Based on these results, a model is proposed for the extracellular production of hydrogen peroxide by C. subvermispora.